Esperienze italiane sul Dissesto Idrogeologico tra Normativa ed Attuazione - Monacelli, Giuseppina; Spiniello, Olimpia (GEOmedia, 2018)
The prevention of hydrogeological instability is a priority for the country, as is evident from the many recent events that, despite involving territorially restricted areas, have caused significant damage and loss of life. Therefore, it is necessary to reflect on the measures - structural and not - undertaken to mitigate the risk, taking also inspiration from the opportunities offered by the European legislation currently being implemented in Italy. The article examines two case studies, a flood of Aulla and Poggio Ferrato, as examples of some problems of the national territory.